The Weight of Inequality: Variation with Industrialization and Wealth - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2015)
When other economic measurements are scarce or unreliable, height and the body mass index (BMI) are now well accepted measures for cumulative and current net nutrition. However, as the ratio of weight to height, BMI is the ratio of current to cumulative net nutrition, therefore, does not fully isolate changes in current net nutrition. This study uses weight after controlling for height as a measure for current net nutrition and shows that US black and white weights decreased throughout the late 19th and early 20th centuries, were higher in the South, and for farmers and unskilled workers. Like stature and BMI, 19th century weight was higher in states with greater average wealth and population density and lower in states with greater wealth inequality.
Keywords: I10; J11; J71; N31; 330; weight; current net nutrition; wealth; inequality